Creation of micro‐topographic features: a new tool for introducing specialist species of calcareous grassland to restored sites?. Issue 1 (31st August 2015) - Wagner, Markus; Bullock, James M.; Hulmes, Lucy; Hulmes, Sarah; Peyton, Jodey; Amy, Sam R.; Savage, Joanna; Tallowin, Jerry B.; Heard, Matthew S.; Pywell, Richard F.
Abstract: Questions: What types of pre‐sowing disturbance are most suitable to establish specialist forbs of calcareous grassland at previously agriculturally improved restored sites? What impact does management regime have on post‐establishment abundance‐dynamics? Location: Pegsdon Hills, Bedfordshire, UK. Methods: We set up a 4‐yr experiment using a split‐plot design to combine pre‐sowing disturbance treatments at sub‐plot level (undisturbed control, glyphosate spraying, harrowing, and creation of ridge‐and‐furrow features) with three post‐establishment management regimes applied at main plot level in years 2–4, involving either summer cutting or summer cattle grazing, and presence or absence of spring sheep grazing, along with autumn cattle grazing in all regimes. After disturbance application, we sowed a seed mixture containing ten specialist species of calcareous grassland. Using quadrat‐based methods, we monitored first‐year establishment and subsequent dynamics, including reproductive status of species at quadrat level. Initial establishment and subsequent dynamics were analysed separately using LMM. Results: Initial establishment of sown species was promoted both by harrowing and by ridge‐and‐furrow creation. While some species were about equally promoted by both, several other species benefited more strongly or exclusively from ridge‐and‐furrow creation. Effects of disturbance largely persisted in subsequent years, but for some species, different dynamics were observed for harrowed and ridge‐and‐furrow treatments. Thymus pulegioides and Hippocrepis comosa gradually achieved higher abundances in the ridge‐and‐furrow treatment, in which notable levels of bare ground persisted for much longer than in the harrowed treatment. In contrast, Filipendula vulgaris and Pimpinella saxifraga achieved higher abundance in the harrowed treatment. Sown species tended to reach reproductive stage faster in the ridge‐and‐furrow treatment than in the harrowed treatment. By the end of the study, management regimes had resulted in few effects on species dynamics. Conclusions: Establishment of specialist species of calcareous grassland crucially depended on bare ground creation prior to sowing. Ridge‐and‐furrow creation resulted in more persistent reduction of competition than the standard practice of harrowing, provided more suitable conditions for low‐statured specialist species, and generally enabled faster transition of introduced specialist species to reproductive stage. Our results thus illustrate potential benefits of using more severe disturbance when introducing specialist species of calcareous grassland at restored sites. Abstract : We tested the effects of pre‐sowing disturbance techniques and of post‐establishment management regimes on establishment of sown specialist forbs of calcareous grassland in a partially restored site. Both harrowing and creation of micro‐topographic features promoted sown species establishment. The latter technique did however work better for low‐statured species, and generally resulted in faster transition of sown individuals to reproductive stage.